Probiotic Enhanced Intestinal Immunity in Broilers against Subclinical Necrotic Enteritis - Wang, Hesong; Ni, Xueqin; Qing, Xiaodan; Liu, Lei; Lai, Jing; Khalique, Abdul; Li, Guangyao; Pan, Kangcheng; Jing, Bo; Zeng, Dong (Frontiers in Immunology, 2017)
Along with banning of antibiotics, necrotic enteritis (NE), especially subclinical NE (SNE) whereby no clinical signs are present in chicks, has become one of the most threatening problems in poultry industry. Therefore, increasing attention has been focused on research and application of effective probiotic strains, as an alternative to antibiotics, to prevent SNE in broilers. In the present study, we evaluated the effects of Lactobacillus johnsonii BS15 on prevention of SNE in broilers. Specifically, assessment determined growth performance and indexes related to intestinal mucosal immunity in the ileum and cecal tonsil of broilers. A total of 300 one-day-old Cobb 500 chicks were randomly distributed into the following five groups: control group (fed with basal diet + de Man, Rogosa, and Sharpe liquid medium [normal diet]), SNE group (normal diet), BS15 group (basal diet + 1 × 106 colony-forming units BS15/g as fed [BS15 diet]), treatment group (normal diet [days 1–28] + BS15 diet [days 29–42]), and prevention group (BS15 diet [days 1–28] + normal diet [days 29–42]) throughout a 42-day experimental period. SNE infection was treated for all chicks in the SNE, BS15, treatment, and prevention groups. The present results demonstrated that BS15 supplementation of feeds in BS15 and prevention groups exerted a positive effect on preventing negative influences on growth performance; these negative influences included low body weight gain and increased feed conversion ratio caused by SNE. Although no changes were detected in all determined indexes in cecal tonsils, BS15-treated broilers were free from SNE-caused damage in villi in the ileum. BS15 inhibited SNE-caused decrease in immunoglobulins in the ileum. In the lamina propria of ileum, T-cell subsets of lymphocytes influenced by SNE were also controlled by BS15. BS15 affected antioxidant abilities of the ileum and controlled SNE-induced mitochondrion-mediated apoptosis by positively changing contents and/or mRNA expression levels of apoptosis-related proteins. These findings indicate that BS15 supplementation may prevent SNE-affected growth decline mainly through enhancing intestinal immunity in broilers.